2006
DOI: 10.4161/cc.5.16.3092
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Cleavage of Rabaptin-5-like Proteins and a Model for Rabaptin-5 Inactivation in Apoptosis

Abstract: Previously published online as a Cell Cycle E-publication: http://www.landesbioscience.com/journals/cc/abstract.php?id=3092 KEY WORDSendocytosis, Rabaptin-5, Rabaptin-5 isoforms, apoptosis, Rab5 binding site ABBREVIATIONS 3AT3 ABSTRACTIntracellular membrane transport from the plasma membrane is one of the processes affected in apoptotic cells. Apoptotic inhibition of endosomal transport occurs due to cleavage of Rabaptin-5, an effector of small GTPase Rab5, which results in inhibition of early endosome fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…3A). The deletion in Rbpt5Δ4/2 indeed overlaps with a second reported Rab5-interacting segment (residues 216-318; Korobko et al, 2006) that might be inactivated by the deletion in Rbpt5Δ4/2. Expression of Rbpt5δ, a natural splice variant lacking residues 187-226, which hardly cut into the Rab5-interacting segment, did not cause endosome enlargement (Fig.…”
Section: Rab4 Is Required For Rbpt5 Recruitment Through Two Distinct mentioning
confidence: 98%
See 1 more Smart Citation
“…3A). The deletion in Rbpt5Δ4/2 indeed overlaps with a second reported Rab5-interacting segment (residues 216-318; Korobko et al, 2006) that might be inactivated by the deletion in Rbpt5Δ4/2. Expression of Rbpt5δ, a natural splice variant lacking residues 187-226, which hardly cut into the Rab5-interacting segment, did not cause endosome enlargement (Fig.…”
Section: Rab4 Is Required For Rbpt5 Recruitment Through Two Distinct mentioning
confidence: 98%
“…It was initially isolated as an interactor of Rab5 (Stenmark et al, 1995). It specifically binds Rab5-GTP through a C-terminal domain (residues 814-862; Vitale et al, 1998;Zhu et al, 2004b), but yeast two-hybrid and glutathione-S-transferase (GST)-Rab5 pulldown experiments have also observed some interaction through a second site in the N-terminal part of the protein (Deneka et al, 2003;Vitale et al, 1998), specifically in the segment 216-318 (Korobko et al, 2006). In addition, Rbpt5 associates, through its CC2-1 coiled-coil segment, to Rabex5 (also known as RABGEF1), the GEF of Rab5 (Horiuchi et al, 1997;Mattera et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Rabaptin-5 cleavage has been proposed as a mechanism that can disrupt the endosome compartment during apoptosis. [47][48][49] Although we found no differences in the viability of mast cells in standard culture media, Rabaptin-5-deficient BMCMCs were more susceptible to apoptosis after growth factor withdrawal ( Figure S8). Future studies will be required to characterize in detail Rabaptin-5's role in cell survival.…”
Section: Discussionmentioning
confidence: 78%
“…18 A second Rab5 binding site was discovered in the N-terminal half of Rabaptin5 near CC1-2 by yeast 2-hybrid screening. 19 Furthermore, in vitro and in vivo studies identified binding sites for the GAT domain (domain found in GGAs and TOM1) of GGAs (Golgi-localized, g-ear-containing, ARF-binding proteins) and g-adaptin ear (GAE) domains of AP-1 and GGAs. 20 Their function was proposed to be the regulation of AP-1 or GGA dependent vesicle transport at endosomes.…”
Section: Feedforward Instead Of Feedback For Rab5 Activationmentioning
confidence: 99%